PENGEMBANGAN MODEL E-GOVERNMENT DALAM PELAYANAN PUBLIK - Awang Anwaruddin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The system of public service developed by the Indonesian government is characterized by a centralized top-down monopoly model. The so-called functional, centralized, and integrated model of public service is merely a type of delegation of authority from central government to linked public service institutions without involving the society, especially in terms of interaction and transaction between the government and society in a free way, without delimited by cost, time and space, aswell as the choice of service type and facilities. Thus, it is time for the government to increase the quality of public service through the reformulation of policies that may fulfill the increasing demands of changing era and the development of more strategic infrastructure an facilities, among others, implementing EGovernmentas an effort to facilitate an interaction between the government and society, which we believe as the significant factor of an ideal model of public service.